Longitudinal neuroimaging following combat concussion: sub-acute, 1 year and 5 years post-injury. Issue 1 (5th November 2019) - Mac Donald, Christine L; Barber, Jason; Andre, Jalal; Panks, Chris; Zalewski, Kody; Temkin, Nancy
Abstract: Questions remain regarding the long-term impact of combat concussive blast exposure. While efforts have begun to highlight the clinical impact, less is known about neuroimaging trajectories that may inform underlying pathophysiological changes post-injury. Through collaborative efforts in combat, following medical evacuation, and at universities in the USA, this study followed service members both with and without blast concussion from the sub-acute to 1-year and 5-year outcomes with quantitative neuroimaging. The following two primary and two exploratory groups were examined: combat-deployed controls without blast exposure history 'non-blast control' and concussive blast patients (primary) and combat concussion arising not from blast 'non-blast concussion' and combat-deployed controls with blast exposure history 'blast control' (exploratory). A total of 575 subjects were prospectively enrolled and imaged; 347 subjects completed further neuroimaging examination at 1 year and 342 subjects completed further neuroimaging examination at 5 years post-injury. At each time point, MRI scans were completed that included high-resolution structural as well as diffusion tensor imaging acquisitions processed for quantitative volumetric and diffusion tensor imaging changes. Longitudinal evaluation of the number of abnormal diffusion tensor imaging and volumetric regions in patients with blast concussion revealed distinct trends by imaging modality. While the presence of abnormal volumetric regions remained quite stable comparing our two primary groups of non-blast control to blast concussion, the diffusion tensor imaging abnormalities were observed to have varying trajectories. Most striking was the fractional anisotropy 'U-shaped' curve observed for a proportion of those that, if we had only followed them to 1 year, would look like trajectories of recovery. However, by continuing the follow-up to 5 years in these very same patients, a secondary increase in the number of reduced fractional anisotropy regions was identified. Comparing non-blast controls to blast concussion at each time point revealed significant differences in the number of regions with reduced fractional anisotropy at both the sub-acute and 5-year time points, which held after adjustment for age, education, gender, scanner and subsequent head injury exposure followed by correction for multiple comparisons. The secondary increase identified in patients with blast concussion may be the earliest indications of microstructural changes underlying the 'accelerated brain aging' theory recently reported from chronic, cross-sectional studies of veterans following brain injury. These varying trajectories also inform potential prognostic neuroimaging biomarkers of progression and recovery. Abstract : Patients with and without blast concussion were evaluated at sub-acute, 1-year and 5-year outcomes to investigate long-term neuroimaging blast sequelae. Analysis revealed significant differences in the number of reduced fractional anisotropy regions at sub-acute and 5-year outcomes. The secondary increase may provide insight into changes underlying the 'accelerated brain aging' theory. Graphical Abstract: